2005
DOI: 10.1063/1.1846947
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of oxygen vacancy induced phenomena in ferroelectric thin films

Abstract: The role of oxygen vacancy in lead-titanate-zirconate ferroelectric thin film has been numerically simulated using the two-dimensional four-state Potts model. On one hand, the presence of an oxygen vacancy in a perovskite cell strongly influences the displacement of the Ti 4+ ion. Hence the vacancy-dipole coupling must be considered in the switching mechanism. On the other hand, a space charge layer is established by the inhomogeneous distribution of oxygen vacancies through trapping charge carriers. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The details of this model have been described before. 6,13 The film is represented by the two-dimensional array of cells in xz plane. The size of the system is N x N z , where N x and N z are the numbers of cells along the x and z axes, respectively.…”
Section: Theory and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of this model have been described before. 6,13 The film is represented by the two-dimensional array of cells in xz plane. The size of the system is N x N z , where N x and N z are the numbers of cells along the x and z axes, respectively.…”
Section: Theory and Modelingmentioning
confidence: 99%
“…The system is initially unpoled and the initialization of the system of pseudospins has been discussed previously. 13 In order to simulate a film of finite thickness and of infinite width, free boundary condition is applied for both the top ͑j =1͒ and bottom ͑j = N z ͒ surfaces, and periodic boundary condition is adopted along the transverse direction. The film is subject to the alternating external electric field and stress which have the following common properties: ͑1͒ longitudinal, ͑2͒ triangular wave form, ͑3͒ of the same frequency, and ͑4͒ uniform in space.…”
Section: ͑3͒mentioning
confidence: 99%
“…For example, the presence of oxygen vacancies enhances the coercive field, 7,8 creates imprint effect by shifting the polarizationelectric field ͑P-E͒ loop along the electric field axis, 7,9 and causes polarization fatigue effect. 10,11 There are also a number of reports on the occurrence of double hysteresis loops in the presence of oxygen vacancies. [9][10][11][12][13] Ren 14 has presented a qualitative explanation for the presence of double hysteresis loop by considering the conformal alignment of defect dipoles along the spontaneous polarization P S direction imposed by the crystal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 There are also a number of reports on the occurrence of double hysteresis loops in the presence of oxygen vacancies. [9][10][11][12][13] Ren 14 has presented a qualitative explanation for the presence of double hysteresis loop by considering the conformal alignment of defect dipoles along the spontaneous polarization P S direction imposed by the crystal symmetry. Each of these dipoles is created by oxygen vacancy in the perovskite cell.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is observed that the switchable polarization of PZT films decreases when the PZT films are used for increased number of bipolar-voltage cycles. [6][7][8][9][10] This reduction in the switchable/remnant polarization, i.e. fatigue, limits the reliability and usage of the PZT films in device applications.…”
Section: Introductionmentioning
confidence: 99%